Diabetes mellitus e doença periodontal: revisão de literatura - Szendler, Cristina Baladore [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Diabetes mellitus is an important chronic disease globally as reflected in the World Health Organization (WHO) declaring that the rate of increase in diabetes prevalence is an epidemic. In 2005, it was estimated that 217 million people were diabetic worldwide. By 2030 WHO predicts this number to increase to at least 366 million (Smyth and Heron, 2006). Current evidence regarding the biologic link between diabetes and periodontal disease supports diabetes and persisting hyperglycemia leading to an exaggerated immuno-inflammatory response to the periodontal pathogenic bacterial challenge resulting in more rapid and severe periodontal tissue destruction. Periodontitis may also be related to the glycemic control in diabetes because inflammation can increase insulin resistance. The purpose of this study is to address the relationship between diabetes mellitus and periodontal disease, as well as the plausible biologic mechanisms that support this link

O diabetes mellitus é uma doença crônica e de acordo com a Organização Mundial da Saúde (OMS, 2005), o aumento na prevalência de casos desta doença tornou-se uma epidemia. Em 2005, foram estimados 217 milhões de casos de indivíduos acometidos pelo diabetes em todo o mundo. A OMS acredita que, em 2030, a prevalência do diabetes será de no mínimo 366 milhões de casos. Atualmente, existem evidências da ligação biológica do diabetes com a doença periodontal, podendo a hiperglicemia persistente ocasionar uma resposta imune exacerbada aos patógenos periodontais, resultando em destruição mais rápida e severa do periodonto. A periodontite pode também estar relacionada ao controle glicêmico no diabetes, uma vez que a inflamação pode ocasionar um aumento na resistência à insulina. Este trabalho tem por objetivo abordar a relação entre o diabetes mellitus e a doença periodontal, bem como os mecanismos biológicos plausivos que sustentam esta relação
Keywords: Diabetes mellitus; Doenças periodontais; Periodontite; Periodontal diseases